Enhancing Students' Vocabulary Mastery through Kahoot-Based Formative Assessment - Zahratul Fikni; Baiq Almalia Lestari; M. Junaidi Marzuki; Laila Wati (Mataram University, 2026)
This study aimed to determine the effect of Kahoot-based formative assessment on students' vocabulary mastery and to describe the relationship between students' Kahoot scores and their post-test results. This study examined the effect of Kahoot-based formative assessment on tenth-grade students' vocabulary mastery at MA NW Kotaraja in the academic year 2025/2026. This studies examine whether the use of Kahoot-based formative assessment significantly improved students' vocabulary mastery, and how students' Kahoot scores related to their post-test results. This study used a pre-experimental design with a one-group pre-test post-test approach. The sample consisted of 22 students selected through purposive sampling from a total population of 92 tenth-grade students. Data were collected through a pre-test, five Kahoot-based formative assessment sessions covering 50 daily activities vocabulary items, a post-test, and brief interviews with six selected students. The pre-test and post-test each consisted of 50 multiple-choice items with a maximum score of 100. Data were analyzed using the Shapiro-Wilk normality test, the Wilcoxon Signed-Rank Test, effect size calculation, and descriptive comparison. Results showed statistically significant improvement in vocabulary mastery with p = 0.028 and effect size r = 0.47, indicating a medium effect. The mean score increased from 60.45 to 77.64. Descriptively, 81.8% of students with high Kahoot scores achieved good or very good post-test results. These findings confirm that Kahoot-based formative assessment effectively enhances EFL students' vocabulary mastery.